Crystallization of double crystalline diblock copolymer from microphase separated melt. (21st October 2019) - Kundu, Chitrita; Joshi, Nikhil S.; Dasmahapatra, Ashok K.
Abstract: Diblock copolymers by virtue of the chemical dissimilarity between the constituting blocks exhibit microphase separation in the melt state. The phase separated melt can successfully be exploited to control the morphology of the final semi crystalline materials by allowing an extended thermal annealing, which accelerates coalescence of microdomains. Herein, we report simulation results on the crystallization behavior of A‐B diblock copolymer, wherein the melting temperature of A‐block is higher than B‐block, instigated from microphase separated melt. During crystallization, the morphological evolution of microphase separated melt is extensively driven by thermal history. Isothermal crystallization confines crystallization in phase separated microdomains, whereas nonisothermal crystallization results in morphological perturbation of melt microdomains. Annealing of microphase separated melt successfully reorients melt morphology, where isothermal as well as nonisothermal crystallization retains the melt morphology intact due to the hard confinement resulted during microphase separation. The rate of crystallization of microphase separated annealed melt is much faster than microphase separated melt without annealing due to more relaxed structure of microphase separated melt achieved through the process of annealing. Two‐step compared to one‐step isothermal crystallization yields higher crystallinity of A‐block with thicker crystals whereas crystallinity and lamellar thickness of B‐block remains same for both the processes. Abstract : The crystallization behavior of diblock copolymers instigated from microphase separated melt is explored by dynamic Monte Carlo simulation. Dynamic Monte Carlo simulation is one of the potential tools of use to study the phase transition of a polymer. The influence of thermal history determines the final crystal morphology of the diblock copolymers. Thermal annealing endorses coalescence of melt microdomains with more relaxed structures, which remain intact after nonisothermal crystallization. In contrast, microphase separated melt without annealing offers morphological perturbation during nonisothermal crystallization. The rate of crystallization of microphase separated annealed melt is much faster than microphase separated melt without annealing due to the more relaxed structure of microphase separated melt achieved through the process of annealing.